Losses Approximation for Soft Magnetic Composites Based on a Homogenized Equivalent Conductivity - Ren, X.; Corcolle, R.; Daniel, L. (Advanced Electromagnetics, 2016)
Soft magnetic composites (SMC) are a promising alternative to laminated steel in many Electrical Engineering applications. This is largely owing to their low level of eddy current losses. The electromagnetic behavior of SMC in electromagnetic devices cannot be easily predicted using standard numerical techniques such as the finite element method, mostly due to the computational cost required to model the material microstructure. Another difficulty lies in the high property contrast between the matrix and the inclusions. In this paper we propose a homogenization strategy to define the equivalent electromagnetic properties of SMC. For components made of SMC, the equivalent conductivity and permeability can be determined. These equivalent properties can be used to calculate eddy current losses or introduced into structural analysis tools to design electromagnetic devices.